Laparoscopic resection of gastrointestinal stromal tumors of the stomach - Ríos, Alfredo; Boulin, Facundo; Pastorino, Martín; Correa, Agustín; Fiolo, Felipe E. (Revista Argentina de Cirugía, 2022)
Introduction: gastric GISTs are rare neoplasms that require a complete resection for cure. Although feasibility of minimally invasive resection has been shown, oncological efficacy is not entirely clear. Objective: to evaluate the safety and efficacy of laparoscopic resections of gastric GIST. Methods: between January 1998 and June 2011, 15 patients with gastric GIST were operated on by laparoscopic resection in our institution. Epidemiology, presentation form, surgical parameters such as conversion rate, intraoperative complications, postoperative morbidity and mortality, hospital stay and follow up were analyzed from our medical records. Results: mean age at presentation was 72.1 years (range 45-89 years), 93.3% of patients were over 60 years, the prevalence of female sex was 10/15 (66.7%). The most common clinical presentation was upper gastrointestinal bleeding 6/15 (40%), followed by dyspepsia / epigastric pain 4/15 (26.7%), and incidental finding in 5 / 15 (33.3%). The tumor was predominantly found in the 2 proximal thirds of the stomach (12/15: 80%). The conversion rate was 1/15 (6.7%) due to hemodynamic instability. In all cases, atypical gastric resection was performed, with direct closure of the defect. Postoperative morbidity and mortality were both 2/15 (13.3%). Neither of the complications was intra-abdominal; one was a stroke and another was an acute myocardial infarction. The average hospital stay was 4 days (range 3-6). The tumor margins were greater than 1 cm in 13/15 cases (86.7%), and marginal in 2 cases. The average tumor size was 4.65 cm (range 1- 11.5 cm).